Enterprise Architecture Design of Local Government Using OADP (Oracle Architecture Development Process) Case Study: Regional Government of Garut Regency - Nugraha, Yopi; Maulani, Galih Abdul Fatah; Amalia, Ai Didah; Mutia, Acep Sandi (Entrepreneurship Faculty, Universitas Garut, 2023)
Garut Regency Regional Government is one of the non-profit organizations that has long utilized information systems and information technology. However, currently, many information systems fail to be implemented due to various reasons. These failures are measured in percentages of 35% total failure, 50% partial failure and 15% success, Judging from the statistical data of the district assessment of the best SPBE implementation in 2022, Garut Regency is not included in the index, meaning that the Garut Government is still below the top 10 of the overall index average. From the various exigencies found, this research was conducted to produce an Enterprise Architecture design using the Oracle Architecture Development Process as a way to facilitate the alignment of business strategies with Information Technology strategies and their implementation. To achieve the research objectives, the Oracle Architecture Development Process method approach is used in which there are several design phases in the form of vision architecture, current state architecture, future state architecture, strategic roadmap, architecture governance, and business cases. So that a blueprint is produced with four main components of architecture, namely business architecture, data architecture, application architecture, and technology architecture which are adjusted to the goals and business processes of the Garut Regency Government. And produced nine recommended applications to support government public service activities, and produced an IT Roadmap that is used to assist in implementing enterprise architecture design and integrating business processes and Government applications. The results of this study are expected to be used as a comparison and guide for the Garut Regency Regional Government in developing information technology in applications, data, and technology, it is hoped that further research will design the business case phase so that the proposals given can be implemented by the Garut Regency Regional Government as a whole.